Dental fear/anxiety in Czech preschoolers: relationship to gender, age, location of residence, dental status and previous treatment experience - Vasakova, J; Tichy, A; Duskova, J; Bradna, P; Broukal, Z (European journal of paediatric dentistry, 2022)
AIM: Dental fear/anxiety (DFA) may considerably complicate treatment in paediatric dentistry. This cross-sectional study aimed to assess DFA in Czech preschoolers aged 3-6 years and its relationship to gender, age, location of residence, dental status and previous treatment. METHODS: The study involved 460 children from preschools in four location types selected according to the WHO criteria for oral health surveys. DFA was assessed using the Venham picture test (VPT, score range 0-8) prior to the evaluation of dental status using the dmfs (decayed, missing, filled surface) index. The significance level was set to 5%. CONCLUSION: DFA is common in Czech preschoolers. Higher levels of DFA were found in females, children aged 3-4 years, children from rural areas, children with a higher dmfs index and children who had a tooth extracted.
Keywords: Dental Caries; Oral Health; Eastern European People; Humans; dítě; DMF Index; Child; Female; Východoevropané; strach z ošetření zubů; orální zdraví; lidé; předškolní dítě; zubní kaz; ženské pohlaví; Cross-Sectional Studies; Child, Preschool; průřezové studie; Dental Anxiety